STRENGTHENING THE ORGANIZATIONAL CULTURE OF UMKM FOR BUSINESS SUSTAINABILITY IN THE KAMU VILLAGE MARKET OLD DENAI, PANTAI LABU DISTRICT DELI SERDANG REGENCY - Tapi Rondang Ni Bulan; Sarah Imelda; Azwansyah Habibie; Muslim Harahap; Bunga Aditi (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
Micro and Small Enterprises (MSEs) have role strategic in support growth economy area , creating field work , and improve welfare society . However , some large number of MSMEs operating in traditional markets Still face various challenges , such as weak governance​ effort , low commitment to standard services , as well as Not yet optimally implementation values culture organizations that can support sustainability business . Condition This was also found among MSMEs at Kamu Market, Denai Lama Village, Pantai Labu District , Deli Serdang Regency . devotion to public This aim For increase understanding and awareness MSME actors regarding importance culture organization as foundation in guard sustainability and power competition business . The method used covering socialization , counseling , discussion interactive and mentoring simple to participants . Activities implemented through stages preparation , implementation , and evaluation . Results of activities show existence improvement understanding participant about values culture organization like discipline , responsibility answer , work same , orientation service and commitment to quality effort . Participants also demonstrated high enthusiasm​ during activity ongoing as well as state readiness For apply values culture organization in activity his business . Activities This give contribution positive in build awareness MSME actors for develop more effort​ professional , adaptive , and sustainable .